The Effectiveness of Retelling Short Story towards Students’ Accuracy in Speaking Skill - Nur Hasanah Safei (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2020)
The objectives of this research is to find out the effectiveness of retelling short story toward students’ accuracy in speaking skill. This research employed pre-experimental method which entails pre-test, treatment, and post-test. Speaking test was used in collecting the data. A total of 39 students of MTsN Makassar as the subject of this research.. The data on the students’ speaking skill were analyzed using descriptive and inferential statistics. The results demonstrated that there was a differentiation between the students’accuracy in speaking skill before and after being thought through retelling short story. The null hypotesis (H0) was rejected and the alternative hypothesis (HI) was accepted because the t-test value was 5,42 which was higher than t-table value 2,024.. The mean score of the students before teaching retelling short story was 2,95 classified as poor score. After teaching retelling short story the mean score was 3,38 classified as a good score. Based on result of data analysis above, the researcher drew conclusion that retelling short story could effective toward students’ accuracy in speaking skill.